1994
DOI: 10.1177/019372394018002004
|View full text |Cite
|
Sign up to set email alerts
|

Gender Equity in Sports Media Coverage: A Review of the Ncaa News

Abstract: To determine the extent to which coverage of male and female collegiate athletes, coaches, and their sports have been similar in the NCAA News, a review of relevant (related to athletes, coaches, or sport events) articles and all pictures from selected issues published in 1988 and 1991 was conducted. In addition to a direct comparison of space allotted to male and female athletes, coaches and their sports, the location of all articles and pictures was examined. With respect to the allocation of space, 297 para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…The chi-square test is commonly used in content analysis (Pedersen 2002a). This research does not attempt to determine if there is equitable representation of males and females in the CrossFit Journal as such a determination would require an independent standard to compare against (Shifflett and Revelle 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The chi-square test is commonly used in content analysis (Pedersen 2002a). This research does not attempt to determine if there is equitable representation of males and females in the CrossFit Journal as such a determination would require an independent standard to compare against (Shifflett and Revelle 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Media representations of women's sport still remain marginal (Baker & Boyd, 1997), and the underrepresentation of female athletes is well documented in studies involving newspapers (Crolley & Teso, 2007;Crossman, Hyslop, & Gutrie, 1994;King, 2007;Pirinen, 1997), the tabloid press (Harris & Clayton, 2002), newspaper photographs (Pedersen, 2002), and TV news (Shifflett & Revelle, 1994). Exceptions are studies of Olympic Games media coverage in which content analysis found no significant gender differences (Capranica & Aversa, 2002;Capranica, Minganti, Billat, et al, 2005;Vincent, Imwold, Masemann, & Johnson, 2002).…”
Section: Hegemonic Masculinity and Media Constructionsmentioning
confidence: 99%
“…The gender aspect is striking: Women clearly receive less publicity than do men, which is a general phenomenon across the sporting world (Crossman, Hyslop, & Gutrie, 1994;Duncan & Messner, 1998;Harris & Clayton, 2002;Pedersen, 2002;Shifflett & Revelle, 1994). Both female and male wrestlers admitted that the women's share of press coverage was almost zero, in particular in the national press/TV, although their successes have certainly deserved attention.…”
Section: Local Press Versus National Press and Tv Coverage Of Wrestlingmentioning
confidence: 99%
“…In relation to gender, there has historically been less coverage of female athletes in the media than their male counterparts (Shifflett & Revelle, 1994). Indeed, this is borne out by a content analysis of newspaper images from around the world the day after the opening ceremony of the 2012 London Olympics which found that in the British media men Tangible differences in the ways in which men and women in sport are commentated on have also been identified, but not as yet in relation to the London Olympics.…”
Section: Media Coverage Of Female and Non-white Athletesmentioning
confidence: 99%